The impact of volume and gelling on the physiological and appetitive responses to nutritional support products - Aliyu, Abdulsalam Ibrahim (2022)
Undernutrition is still a major clinical problem in patients who are unable to feed normally through the oral route or unable to meet their nutritional requirement via oral feeding alone. Oral nutrition supplements (ONS) and nasogastric tube feeds (NGTF) are widely used to improve nutritional intakes in such patients. However, these types of nutritional interventions are affected by several factors related to their use like poor compliance and suppression of food intake and complications of diarrhoea and gastro-oesophageal reflux (GOR). Strategies are needed to optimise the acceptability of ONS and improve tolerance of these products in order to achieve nutritional targets in the affected people. Manipulation of the formulation of the ONS drinks and tube feeds, to alter their physical and chemical characteristics, may offer the opportunity to optimise additional food intake, or suppress hunger, as clinically indicated. This thesis work aimed to explore the impact of specific physical (volume) and chemical/ physical properties (addition of an alginate that forms a gel in acidic conditions) of ONS and NGTF, on total nutritional intake and indicators of complications associated with NGTF (diarrhoea and GOR). Two major studies were carried among young healthy males (chapters 3, 4 and 5) and females (chapter 3) to verify the objectives of the thesis. The study in chapter 3 tested the effect of consuming two different volumes of isoenergetic (300kcal) ONS drinks in 10 healthy males and females, with measurements of total daily energy intake, oro-sensory attributes, and appetite responses, whilst the study of chapters 4 and 5 compared the impact of alginate (a fibre that forms a gel under acidic conditions of stomach) and inulin (a gel-free fibre under acidic conditions) in NGTF in 10 healthy males using MRI and hormone assays to measure small bowel water content (SBWC), gastrointestinal, endocrine, and appetitive responses. Consumption of a smaller volume (more energy dense) ONS drink twice daily for 7 consecutive days resulted in a numerically higher energy intake (202kcal ±365) than the larger less energy dense ONS drink, without significantly affecting the appetite sensations in the participants. Data collected allowed a power calculation to be undertaken. Twenty-nine participants would be required to detect a 200kcal difference with 80% power and a significance level of p <0.05. Intake of 300ml of alginate containing NGTF over 1 hour resulted in a significantly lesser reduction in SBWC, faster reduction in gastric volume, lower insulin, PYY and incretin responses, with no difference in glycaemic response, GOR symptoms, satiety feelings or appetite sensations compared with the alginate-free feed. The study on the use of ONS demonstrated the feasibility of the protocol. The results must be interpreted with caution given the small sample size but have enabled us to predict the sample size required for future studies to confirm if energy delivery is improved with a small volume which would be potentially important over a longer duration. Similarly, the study on the use of alginate in NGTF has shown the potential to understand the effect of gel formation by alginate using non-invasive MRI and gut hormone responses to measure of gastrointestinal functions.